Operation of Freight Forwarders and Adoption of Rail Inter-Terminal Transfer System for Containerised Cargo Movement of Tanjung Pelepas Port, Malaysia - Halil, Ali (2024)
This dissertation explores the application of the Technology Acceptance Model (TAM) in the context of rail interterminal transportation. Utilizing the TAM framework, the study tests various hypotheses and research questions through extensive statistical analysis. Data was collected via surveys conducted among freight forwarding companies and analysed using SPSS software. The results demonstrate that the original TAM model, along with its subsequent iterations, effectively predicts and explains user acceptance of technology within rail interterminal transfer operations. The analysis identified perceived usefulness and perceived ease of use as the primary dimensions influencing technology adoption. Additionally, secondary dimensions such as privacy, perceived security, perceived trustworthiness, and perceived capability also significantly impact user acceptance. Correlation analysis showed that all null hypotheses were accepted except 1, indicating relationships among the variables as posited by the model. However, regression analysis revealed the presence of additional factors that may influence the outcomes, suggesting the complexity of technology adoption in this context. Based on these findings, several recommendations are proposed. These recommendations address the results derived from the demographic analysis, correlation analysis, and regression analysis, offering actionable insights for improving technology acceptance in rail interterminal transfer operations.